Efeitos da cirurgia ortognática bimaxilar em pacientes com e sem dtm muscular : estudo retrospectivo - Velasques, Bibiana Dalsasso (2021)
Orthognathic surgery (OS) is listed as one of the treatments for muscular temporomandibular disorder (TMD), however, real effects and its effectiveness as treatment, is still controversial. The aim of this study was to evaluate the effects of CO on the temporomandibular joint (TMJ) space of patients with without muscle pain (G0) and persistent pain (G0). The effects over TMJ were analyzed through, computed tomography cone beam scans of the face superimposed following the protocol based on voxel and linear measurements of the left and right TMJ space were performed in the preoperative period (T0) and in the postoperative period (T1). Furthermore, the types of movements performed in the OS were evaluated. Pearson's chi-square test (χ2) was used to correlate the movements of OS with the TMJ space. The study showed a change in condylar positioning £1mm, with no statistically significant difference between the groups or type of movement performed during OS and the changes caused in TMJ space. Muscle TMD symptomatology were reduced to low level complain without the use of medications. Thus, it was concluded that the set of movements performed in OS promote TMJ space stability, which contributes to a reduction in the previous muscle TMD, but there was no conclusive evidence of the effects of OS in the reduction of muscular TMD.